C-Type Natriuretic Peptide Pre-Treatment Improves Maturation Rate of Goat Oocytes by Maintaining Transzonal Projections, Spindle Morphology, and Mitochondrial Function - Rui Xu; Menghao Pan; Lu Yin; Yiqian Zhang; Yaju Tang; Sihai Lu; Yan Gao; Qiang Wei; Bin Han; Baohua Ma (Animals, 2023)
C-type natriuretic peptide (CNP) is a peptide molecule naturally found in follicles and can be used to extend meiotic resumption and enhance the potential for oocytes to develop. However, the mechanism by which CNP improves goat oocyte quality remains unclear. In this study, cumulus–oocyte complexes (COCs) from goats were pre-treated with CNP prior to IVM, and the results showed that pre-treatment with CNP enhanced goat oocyte maturation. First, we discovered that CNP maintained communication between cumulus cells and oocytes by regulating the transzonal projections (TZPs). We then found that CNP treatment reduced abnormal spindle formation and increased the expression of genes associated with spindle assembly and the spindle assembly checkpoint. Moreover, further analysis showed that oocytes exhibited better antioxidant ability in the CNP treatment group, which mainly manifested in higher glutathione (GSH) and lower reactive oxygen species (ROS) concentrations. Enhanced mitochondrial activity was signified via the augmented expression of mitochondrial oxidative metabolism and fusion and fission-related genes, thus diminishing the apoptosis of the oocytes. Overall, these results provide novel insights into the potential mechanism by which CNP treatment before IVM can improve oocyte quality.